2016
DOI: 10.1186/s12951-016-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Membrane roughness as a sensitive parameter reflecting the status of neuronal cells in response to chemical and nanoparticle treatments

Abstract: BackgroundCell membranes exhibit abundant types of responses to external stimulations. Intuitively, membrane topography should be sensitive to changes of physical or chemical factors in the microenvironment. We employed the non-interferometric wide-field optical profilometry (NIWOP) technique to quantify the membrane roughness of living neuroblastoma cells under various treatments that could change the mechanical properties of the cells.ResultsThe membrane roughness was reduced as the neuroblastoma cell was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…4e, f) indicated that the roughness of the dehydrated CDs-fed cells was ∼49% higher than that of the pristine cells (104.3 ± 28.1 nm vs. 70.0 ± 22.1 nm, n = 24). According to the literature 19,20 , in addition to the attachment on the cell surface, the profile of intracellular particles or their clusters (with size detectable by AFM) can be reflected from the varied roughness of dehydrated cells, as the cells have lost the flexible and malleable cytoskeleton. To further explore whether the CDs were attached on the cell surface specifically or also being able to distribute inside the cells, cryo-electron tomography was employed.…”
Section: Resultsmentioning
confidence: 99%
“…4e, f) indicated that the roughness of the dehydrated CDs-fed cells was ∼49% higher than that of the pristine cells (104.3 ± 28.1 nm vs. 70.0 ± 22.1 nm, n = 24). According to the literature 19,20 , in addition to the attachment on the cell surface, the profile of intracellular particles or their clusters (with size detectable by AFM) can be reflected from the varied roughness of dehydrated cells, as the cells have lost the flexible and malleable cytoskeleton. To further explore whether the CDs were attached on the cell surface specifically or also being able to distribute inside the cells, cryo-electron tomography was employed.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, membrane roughness is modulated by way of actin filaments in cells responding to substrate properties. In our previous work, we showed that the membrane roughness of neuronal N2a cells was sensitive to the treatment of a microtubule-stabilization drug paclitaxel (Taxol) 12 . Here we also tested the effect of Taxol on the membrane roughness in MEFs and found that the Taxol treatment for 4 hours had no significant effect on the membrane roughness (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous works 3 , 12 , we demonstrated that the membrane roughness of neuroblastoma cells is sensitive to various external stimulations, including amyloid peptides of different conformations, electric fields, an anti-cancer drug Taxol, gold nanoparticles, and a hypertonic solution. Nonetheless, the treatments used in those previous works were all solution-based.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The plane fit more accurately revealed surface roughness. Recently, Lee et al [58] demonstrated that Taxol-induced decrease in the roughness of neuroblastoma cells indicates an increase of membrane stiffness caused by microtubule translocation. In addition, they showed a time-lapse measurement of the decrease in membrane tension induced by a hypertonic solution that resulted in an increase of membrane roughness.…”
Section: The New Biomarkers For Identifying the Neuroprotective Effecmentioning
confidence: 99%